WASTI SEBAGAI KRITIK IDEOLOGI - Robert Setio (Studia Philosophica et Theologica, 2011)
This article discusses the figure of Vashti, the banished queen in the book of Esther for her refusal to appear at a party hosted by King Ahasueros for his quests. Vashti is a marginal figure in the book and often misjudged as liberal, vain, and wicked. Yet, the writer argues that Vashty can be an inspiration for women and minority groups. Feminist view of Vashti, the writer argues, has opened the possibility to revise the negative view of Vashti. Traditional view, that exalts Esther, actually perpetuates patriarchal system. Instead of Esther, Vashti is more suitable to be a role-model because she dared to challenge the patriarchal system. She can also be a model for minorities for her courage to defend her integrity. Vashti’s example can inspire minorities to stand up for their identity and defend their integrity against unfair threats from the majority. This, for sure, requires enough courage to take risk. Nevertheless, this is not really an option because people who do not have courage to defend their integrity has lost their humanity.